Aktualisasi Diri dan Persepsi Terhadap Pelaksanaan Pelatihan Pada Karyawan - Ellyana Pratika; Ni Wayan Sukmawati Puspitadewi (Jurnal Psikologi Teori dan Terapan, 2014)
This study was aimed to determine the relation between self-actualization and the perception of employees’ training implementation in PT Pelindo III Gresik branch. This study method was a correlational research. The subjects were 46 employees of PT Pelindo III Gresik branch. Data collected using self-actualization and perception of training implementation Likert scale. Data analysis technique used in this study was Pearson correlation product moment with the help of SPSS 16 for windows. The result shows that the significant value (p) is 0.000, while the value of the correlation (r) is 0.651. The result shows that  the significance value of the correlation is less than 0.05 (p = 0.000 <0.05)which means the hypothesis of this study is significantly proven. It can be concluded from the result there is a significant relation between self-actualization and the perception of employees’  training implementation in PT Pelindo III Gresik branch.